Utilization of Lignocellulosic Waste as a Source of Liquid Smoke: A Literature Review, Lampung, Indonesia - Santiyo Wibowo; Wasrin Syafii; Gustan Pari; Elis Nina Herliyana (Universitas Airlangga, 2023)
Introduction: Lignocellulosic biomass waste will become a problem for environmental health if not managed correctly. Biomass waste decomposition can produce methane gas which impacts climate change; it can also be a source of breeding pests and diseases. Various efforts have been made to utilize the waste so that it has an added economic value and is environmentally friendly. One of the waste utilization techniques is the carbonization of lignocellulosic biomass into charcoal and liquid smoke. Discussion: A literature review used the articles from Science Direct, Pubmed, Google Scholar, and Research Gate databases over ten years. This literature review paper aims to provide information on producing and utilizing liquid smoke and concludes with some suggestions on production and application. The literature review results show evidence that liquid smoke has been used since the time of the Neanderthals. Then, since the early nineteen century, liquid smoke has been applied in agriculture as plant growth, soil treatment, pesticide, antimicrobial, rubber coagulant/deodorizer, and antioxidant. Conclusion: A significant contribution of liquid smoke utilization is all lignocellulosic biomass waste that can be carbonized into charcoal and liquid smoke so that it can reduce waste problems. Therefore, liquid smoke can reduce the use of pesticides, herbicides, and insect repellents made from synthetic chemicals that can poison the environment. Not much research has been produced and utilized liquid smoke in the pyrolysis temperature stratification technique. So, there are still quite a lot of research opportunities for the diversification of liquid smoke production.